Orthopantomographic evaluation of third molar developmental stages in relation to chronological age of Bangladeshi female garment workers: A case report - Mahmud, Shaikh Zakir; Nomann, Nahid Al; Kabir, Md Arafat; Jan, Chowdhury Moin (Bangladesh Journal of Dental Research & Education, 2015)
Human teeth are among the most distinctive and long lasting features of mammal species. Various quantitative and qualitative methodologies have been developed by the researchers in order to establish an assessment format to determine the correlation between the dental age and the chronological age. The morphological and radiological examinations of third molars make up a part of the orthodontic, pedodontic, forensic odontology and oral surgical treatments and remain the most reliable biologic indicator available for age estimation during the middle teens and early twenties. This age calculation requirement is not only for differentiating the juvenile from the adult status in criminal law cases, but also for chronological age estimation in relation to school attendance, social benefits, employment and marriage. A case for actual need for age estimation using a developing third molar is presented here DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22456 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 22-25